Redox and Light Control the Heme-Sensing Activity of AppA - Liang Yin (American Society for Microbiology, 2013)
ABSTRACT The DNA binding activity of the photosystem-specific repressor PpsR is known to be repressed by the antirepressor AppA. AppA contains a blue-light-absorbing BLUF domain and a heme-binding SCHIC domain that controls the interaction of AppA with PpsR in response to light and heme availability. In this study, we have solved the structure of the SCHIC domain and identified the histidine residue that is critical for heme binding. We also demonstrate that dark-adapted AppA binds heme better than light-excited AppA does and that heme bound to the SCHIC domain significantly reduces the length of the BLUF photocycle. We further show that heme binding to the SCHIC domain is affected by the redox state of a disulfide bridge located in the Cys-rich carboxyl-terminal region. These results demonstrate that light, redox, and heme are integrated inputs that control AppA’s ability to disrupt the DNA binding activity of PpsR. IMPORTANCE Photosynthetic bacteria must coordinate synthesis of the tetrapyrroles cobalamin, heme, and bacteriochlorophyll, as overproduction of the latter two is toxic to cells. A key regulator controlling tetrapyrrole biosynthesis is PpsR, and the activity of PpsR is controlled by the heme-binding and light-regulated antirepressor AppA. We show that AppA binds heme only under dark conditions and that heme binding significantly affects the length of the AppA photocycle. Since AppA interacts with PpsR only in the dark, bound heme thus stimulates the antirepressor activity of PpsR. This causes the redirection of tetrapyrrole biosynthesis away from heme into the bacteriochlorophyll branch.